2017
DOI: 10.32607/20758251-2017-9-3-108-114
|View full text |Cite
|
Sign up to set email alerts
|

Expression Levels of the Uridine-Cytidine Kinase Like-1 Protein As a Novel Prognostic Factor for Hepatitis C VirusAssociated Hepatocellular Carcinomas

Abstract: The expression levels of the two novel oncoproteins uridine-cytidine kinase like-1 (UCKL-1) and mitochondrial ribosomal protein S18-2 (MRPS18-2) were assessed in samples of hepatitis C virus (HCV)-associated hepatocellular carcinoma (HCC) using immunohistochemistry. Tissue microarray (TMA) paraffin blocks were prepared from 42 HCC tumor samples with the corresponding peri-tumor tissues and from 11 tissues of a liver with HCV-induced cirrhosis. We found that the UCKL-1 signal in the liver tissues of the peri-tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
4
1
1
Order By: Relevance
“…However, only UCK2, but not UCKL1 was associated with survival outcomes of HCC patients. Although one previous study found that in hepatitis C virusassociated HCC, high UCKL1 expression might be a prognostic factor for disease recurrence, in combination with age and microvascular invasion (12), we failed to confirm these associations in this study. We guess that the discrepancy might be due to different virus infection status between the patients.…”
Section: Discussioncontrasting
confidence: 88%
“…However, only UCK2, but not UCKL1 was associated with survival outcomes of HCC patients. Although one previous study found that in hepatitis C virusassociated HCC, high UCKL1 expression might be a prognostic factor for disease recurrence, in combination with age and microvascular invasion (12), we failed to confirm these associations in this study. We guess that the discrepancy might be due to different virus infection status between the patients.…”
Section: Discussioncontrasting
confidence: 88%
“…UCKL1 upregulation, age, and microvascular factors could effectively predict cancer recurrence. 33 Myristoylated alanine-rich C kinase substrate-like protein-1 (MARCKSL1) is a conserved membrane-associated gene regulating cell migration, adhesion, secretion, cell shape, and vessel structure during angiogenesis. 34,35 Zhu et al (2019) 36 reported that MARCKSL1 was highly expressed in patients with HCC and short OS.…”
Section: Discussionmentioning
confidence: 99%
“…Only one MRPS18 gene is found in the bacterial genome, while three S18 genes are encoded by the human genome [1]. Earlier, we have shown that the S18-2 protein is expressed at high levels in several tumor tissues, compared to their normal counterpart, such as endometrial [2], breast [3], prostate [4] cancers, hepatocellular carcinomas [5] and in Hodgkin's lymphomas [6]. Moreover, S18-3 is also overexpressed in breast cancer [7] and in Hodgkin's lymphomas [6].…”
Section: Doi: 1032471/exp-oncology2312-8852vol-43-no-316461mentioning
confidence: 99%